Impaired Proliferation of CD8+ T Cells Stimulated with Monocyte-Derived Dendritic Cells Previously Matured with Thapsigargin-Stimulated LAD2 Human Mast Cells - Kalkusova, Katerina; Taborska, Pavla; Stakheev, Dmitry; Rataj, Michal; Smite, Sindija; Darras, Elea; Albo, Julia; Bartunkova, Jirina; Vannucci, Luca; Smrz, Daniel (Journal of immunology research, 2024)
CD8+ T cells are essential for adaptive immunity against infection and tumors. Their ability to proliferate after stimulation is crucial to their functionality. Dendritic cells (DCs) are professional antigen-presenting cells that induce their proliferation. Here, we show that thapsigargin-induced LAD2 mast cell (MC) line-released products can impair the ability of monocyte-derived DCs to induce CD8+ T-cell proliferation and the generation of Th1 cytokine-producing T cells. We found that culture medium conditioned with LAD2 MCs previously stimulated with thapsigargin (thapsLAD2) induces maturation of DCs as determined by the maturation markers CD80, CD83, CD86, and HLA-DR. However, thapsLAD2-matured DCs produced no detectable TNFα or IL-12 during the maturation. In addition, although their surface expression of PD-L1 was comparable with the immature or TLR7/8-agonist (R848)-matured DCs, their TIM-3 expression was significantly higher than in immature DCs and even much higher than in R848-matured DCs. In addition, contrary to R848-matured DCs, the thapsLAD2-matured DCs only tended to induce enhanced proliferation of CD4+ T cells than immature DCs. For CD8+ T cells, this tendency was not even detected because thapsLAD2-matured and immature DCs comparably induced their proliferation, which contrasted with the significantly enhanced proliferation induced by R848-matured DCs. Furthermore, these differences were comparably recapitulated in the ability of the tested DCs to induce IFNγ- and IFNγ/TNFα-producing T cells. These findings show a novel mechanism of MC-mediated regulation of adaptive immune responses.
Keywords: Lymphocyte Activation; Monocytes; monocyty; cytokiny; buněčný receptor 2 viru hepatitidy A; buněčné linie; Humans; Cell Proliferation; Cell Differentiation; Cell Line; CD8-pozitivní T-lymfocyty; Cytokines; aktivace lymfocytů; mastocyty; imidazoly; proliferace buněk; thapsigargin; Thapsigargin; dendritické buňky; lidé; CD8-Positive T-Lymphocytes; Imidazoles; buněčná diferenciace; Mast Cells; Hepatitis A Virus Cellular Receptor 2; Dendritic Cells